2018
DOI: 10.1074/jbc.ra118.002550
|View full text |Cite
|
Sign up to set email alerts
|

Ovalbumin self-assembles into amyloid nanosheets that elicit immune responses and facilitate sustained drug release

Abstract: Amyloids are associated with many neurodegenerative diseases, motivating investigations into their structure and function. Although not linked to a specific disease, albumins have been reported to form many structural aggregates. We were interested in investigating host immune responses to amyloid fibrils assembled from the model protein ovalbumin. Surprisingly, upon subjecting ovalbumin to standard denaturing conditions, we encountered giant protein nanosheets harboring amyloid-like features and hypothesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Nanosheets are two-dimensional (2-D) structures that can be as thin as a single atomic layer up to approximately 100 nm. , Because of their planar nature, they exhibit very high surface area-to-volume ratios, making them well suited for membrane separations, electrodes, and surface display of functional molecules. Nanosheets have been constructed from biomaterials and biomimetic materials, including proteins, , peptoids, , and synthetic polymers for applications such as drug delivery, electronics, biocatalysis, and separations . The synthesis of 2-D structures from biologically active materials, such as enzymes, is challenging because of the necessity of an interface to direct their assembly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanosheets are two-dimensional (2-D) structures that can be as thin as a single atomic layer up to approximately 100 nm. , Because of their planar nature, they exhibit very high surface area-to-volume ratios, making them well suited for membrane separations, electrodes, and surface display of functional molecules. Nanosheets have been constructed from biomaterials and biomimetic materials, including proteins, , peptoids, , and synthetic polymers for applications such as drug delivery, electronics, biocatalysis, and separations . The synthesis of 2-D structures from biologically active materials, such as enzymes, is challenging because of the necessity of an interface to direct their assembly.…”
Section: Introductionmentioning
confidence: 99%
“…To prepare nanosheets from biomolecules under aqueous conditions, the air–water interface is often used as a template to align hydrophobic patches. , For example, nanosheets have been formed in aqueous solutions from amphiphilic peptoids by gentle rocking. ,, First, the hydrophobic moiety aligns on the interface because of the hydrophobic effect. Then, the solution is tilted to a 65° angle causing expansion of the air–water or solvent–water interface.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, adjusting the structure and size of 2D nanomaterials or applying surface chemistry to 2D nanomaterials is a promising approach and has been constantly showing its potential. Although as mentioned before, the selection of different materials will cause different immune responses 47 , our focus is on the means of structural and surface modification. Below, we will list some representative examples including some of those not directly studying cancer immunotherapy but would largely inspire us.…”
Section: Controlling Immune Response By Structure and Surface Modificationsmentioning
confidence: 99%
“…178 As a proof of concept, Tufail et al accidentally found that amyloid nanosheets formed upon shaking of ovalbumin (yield of 67.6%). 179 The nanosheets released the precursor protein gradually and evoked an immune response. Furthermore, as drug carriers, the protein-originated nanosheets were used for the loading of DOX.…”
Section: Other 2d Nanomaterialsmentioning
confidence: 99%
“…A recently published review by Wei and his co-workers has systematically covered the self-assembly process, structural tuning, and applications of 2D biomaterials in various fields, including biosensing and drug delivery . As a proof of concept, Tufail et al accidentally found that amyloid nanosheets formed upon shaking of ovalbumin (yield of 67.6%) . The nanosheets released the precursor protein gradually and evoked an immune response.…”
Section: Other 2d Nanomaterialsmentioning
confidence: 99%